Big data management - García Márquez, Fausto Pedro; Lev, Benjamin (Springer, 2017)
This book focuses on the analytic principles of business practice and big data. Specifically, it provides an interface between the main disciplines of engineering/technology and the organizational and administrative aspects of management, serving as a complement to books in other disciplines such as economics, finance, marketing and risk analysis. The contributors present their areas of expertise, together with essential case studies that illustrate the successful application of engineering management theories in real-life examples.
Keywords: Business.; Management.; Industrial management.; Operations research.; Decision making.; Management information systems.; Operating systems (Computers); Engineering economy.; elektronické knihy; electronic books